Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Disiplin Kerja Karyawan Pada CV. Pelita Offset Jombang - Ardhiansyah, Rahmad; Retno, Mei; Rini, Hesty Prima (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to determine the effect of work motivation and work environment on employee work discipline (case study of CV Pelita Offset Jombang). The population in this study were all employees of CV Pelita Offset Jombang with a total of 53 people. The sampling technique used was the saturated sample method. The questionnaire method used for data collection in this study. This study uses Partial Least Square (PLS) as a data analysis technique. The results show that work discipline is positively influenced by work motivation and work environment as seen from hypothesis testing where work motivation has a t-statistic of 2.879, the work environment has a t-statistic of 10,823. This shows that work motivation and a good work environment will increase the work discipline of CV Pelita Offset Jombang employees